Edukasi Peningkatan Pengetahuan Metode Kontrasepsi Jangka Panjang Pada Pasangan Usia Subur di Dusun Pondok Buak, Kecamatan Lingsar - Nurul Hikmah Annisa; Baiq Ricca Afrida; Ni Putu Aryani; Susilia Idyawati (Universitas Ngudi waluyo, 2022)
Family planning is a national scale program to reduce the birth rate and control the population in a country. This method is very effective for both delaying, spacing or terminating pregnancy. Therefore, the government is trying to increase the use of long-term contraceptive methods (MKJP) but in fact there are more users of Non-MKJP contraception than the use of Long-Term Contraceptive Methods (MKJP). The background of holding this